2012
DOI: 10.1080/09645292.2011.645126
|View full text |Cite
|
Sign up to set email alerts
|

School entrance recommendation: a question of age or development?

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The qualifications of the experts that parents consult with and the evaluation criteria they use while expressing their opinions are very important. When international practices are examined, for example, Horstschräer and Muehler (2014) stated that in Germany, some medical screenings are carried out by field experts of all children who turn six in order to determine whether children are ready for school. Similarly, Kaila (2017) emphasized that the law on the school starting age in Finland is flexible and can be decided according to the medical and psychological examinations of the children.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…The qualifications of the experts that parents consult with and the evaluation criteria they use while expressing their opinions are very important. When international practices are examined, for example, Horstschräer and Muehler (2014) stated that in Germany, some medical screenings are carried out by field experts of all children who turn six in order to determine whether children are ready for school. Similarly, Kaila (2017) emphasized that the law on the school starting age in Finland is flexible and can be decided according to the medical and psychological examinations of the children.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…After screening all 4919 documents using the selection criteria described above, we assessed the remaining 15 articles for eligibility based on title and abstract. We excluded 11 studies that did not consider health outcomes (e.g., since they exclusively focused on cognitive development ( Dhuey et al, 2019 ), learning outcomes ( Chen, 2017 , 2021a , 2021b ), or self-esteem ( Thompson et al, 2010 )), did not use data from LMICs ( Berniell & Estrada, 2020 ; Horstschräer & Muehler, 2012 ; Mühlenweg et al, 2012 ), only considered entry into informal education such as kindergarten (as opposed to entry into primary school) ( Gottfried & Sublett, 2019 ; NICHD Early Child Care Research Network, 2007 ), or were not published at the time of our scoping review (e.g., working paper or thesis ( Meng C, 2019 )). No systematic reviews or meta-analyses were identified which assessed the effect of relative age for grade on several health domains in LMICs.…”
Section: Resultsmentioning
confidence: 99%